How to remain competitive in the trucking business: case of pt lookman bersaudara sukses - Widyatmaja Lookman, Sandra; Dung Do, Anh (The Indonesian Journal of Business Administration, 2016)
AbstractÃ¢â‚¬â€PT Lookman Bersaudara Sukses (LBS) is an Indonesian trucking company. In the trucking business, LBS serves full container load and less-than-container load services. LBS was established in Jakarta in 1978 and started its business as a trader of imported fruit. In 1988, a decade after its establishment, the company decided to shift its focus to be a trucking company, after the two Lookman brothers concluded that fruit business in Indonesia was not as promising as before. In 2014, the company changed its name from Lookman Brothers to PT Lookman Bersaudara Sukses. The service coverage of LBS is focused in Java, transporting customersÃ¢â‚¬â„¢ products from Greater Jakarta area to East Java area, vice versa, and some areas of West and Central Java. In the recent years, the road transportation service companies, especially trucking companies, have grown significantly. Moreover, these trucking companies serve quite similar services from one to another, which are full container load and less-than-container load services. Unfortunately, customers of the trucking companies only pay attention on the on time and safe delivery, the customers donÃ¢â‚¬â„¢t really care about any service differentiation that was given by the trucking companies, like tracking system and GPS implementation that is applied by LBS. Furthermore, the growing number of trucking companies, range from big to small companies, eventually lead to the price war since the companies make efforts to maintain their current customers and acquire new customers. In order to remain competitive in Indonesian trucking business and to bring LBS to be sustained in the future, LBS needs to develop and implement appropriate generic strategy and competitive advantages as well as improve the existing business model canvas. This final project began with external and internal analysis of the company. The external analysis is conducted using PESTEL Framework, PorterÃ¢â‚¬â„¢s Five-Forces Model, and Competitor Analysis. PESTEL Framework analysis shows that trucking business still has business opportunities in Indonesia. PorterÃ¢â‚¬â„¢s Five-Forces Model explains the competition within the industry and shows how intense the rivalry among competitors in the business. Competitor Analysis describes the comparison between LBS and its competitors. Furthermore, the internal analysis consists of Resource-Based View and Business Model Canvas. Resource-Based View shows the competitive advantages of LBS and Business Model Canvas illustrate the comprehensive nine business building blocks of LBS. Customer-based research, using questionnaires and interviews, was conducted to know further customersÃ¢â‚¬â„¢ opinion and assumption on LBS current business strategy and model, the competitive advantages LBS customers need to be provided, the appropriate generic strategy to be implemented in the trucking business, and the improvement on LBS existing business model. After analyzing the result of the research and knowing that LBS needs to improve its existing business strategy, the final project is continued to formulate a set of solutions to find ways for LBS to remain competitive in the trucking business. The business solutions are composed of the appropriate generic strategy, appropriate competitive advantages, proposed business model canvas improvement, and related diversification to be applied by LBS. Moreover, the implementation plan is also prepared in order to achieve LBS above-average performance. By achieving above-average performance, LBS will remain competitive in the trucking business in Indonesia.Ã‚Â Keywords: trucking business, generic strategy, competitive advantage, business model canvas